2023
DOI: 10.3390/cancers15030784
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Class I-II-III PI3Ks in Cancer Therapy: Recent Advances in Tumor Biology and Preclinical Research

Abstract: Phosphatidylinositol-3-kinase (PI3K) enzymes, producing signaling phosphoinositides at plasma and intracellular membranes, are key in intracellular signaling and vesicular trafficking pathways. PI3K is a family of eight enzymes divided into three classes with various functions in physiology and largely deregulated in cancer. Here, we will review the recent evidence obtained during the last 5 years on the roles of PI3K class I, II and III isoforms in tumor biology and on the anti-tumoral action of PI3K inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 147 publications
0
4
0
Order By: Relevance
“…Potential roles of PIK3C2γ in cancer are particularly ill-defined. While some studies in murine pancreatic cancer models even regarded it as a tumor suppressor [33,34], mutations in PIK3C2G were associated with poor prognosis in intrahepatic cholangiocarcinoma [35]. Our data now provide a first hint towards a contribution of PIK3C2γ to invasiveness of HCC.…”
Section: Discussionmentioning
confidence: 55%
“…Potential roles of PIK3C2γ in cancer are particularly ill-defined. While some studies in murine pancreatic cancer models even regarded it as a tumor suppressor [33,34], mutations in PIK3C2G were associated with poor prognosis in intrahepatic cholangiocarcinoma [35]. Our data now provide a first hint towards a contribution of PIK3C2γ to invasiveness of HCC.…”
Section: Discussionmentioning
confidence: 55%
“…We found that PIK3C2α, one of three class II PI3 kinases, is a critical regulator of fibroblast activation in response to TGFβ (Figure 3) and survival against inducers of apoptosis (Figure 2). There is a growing understanding that there is a complex signaling network among the PI3 kinases and crosstalk with other signaling molecules including receptor tyrosine kinases and serine/threonine kinases [22,25,59]. In some cases, deletion or inhibition of one PI3 kinase may be compensated by increased activity of other PI3 kinases.…”
Section: Discussionmentioning
confidence: 99%
“…PI3 kinase signaling regulates cell proliferation, survival, activation, and migration. There are emerging data that complex crosstalk takes place among the PI3 kinase family members [22]. The signaling pathways regulated by PI3 kinases can tightly regulate signaling through other PI3 kinases.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K signaling pathway is a complex series of events initiated at the cellular membrane level, involving tightly regulated mechanisms and involves PI3K, AKT, and mTOR substrates. PI3Ks are divided into three different classes (I-II-II) depending on their structural and specific features [10]. Class I PI3Ks are again subclassified into class IA (PI3Kα, PI3Kβ, and PI3Kδ) and class IB (PI3Kγ) encoded by PIK3CA, PIK3CB, PIK3CD and PIK3CG genes, respectively, consisting of a catalytic p110 subunits (p110α, p110β, p110δ, or p110γ) and a regulatory subunit [11,12].…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%